Effect of Moderate Physical Exercise on Autonomic Balance in Irritable Bowel Syndrome - Tenzin, Karma; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2015)
Background: Altered autonomic balance has been noted in Irritable bowel syndrome Regular physical exercise may cause restoration of autonomic balance in health and disease. Objective: To assess the effect of brisk walking on the autonomic balance by analysis of heart rate variability in patients with Irritable bowel syndrome (IBS). Methods: This prospective study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU) in 2013.Seventy seven male IBS patients aged 20-50 years, were enrolled from Gastroenterology OPD, BSMMU, Dhaka. Twenty eight healthy sedentary male with similar age were control. HRV measures were recorded once prior to exercise and then after 3 months of brisk walking. For assessing autonomic balance, LF/HF ratio and Max/Min RR was evaluated by Polyrite D machine and software. ANOVA, Independent sample t-test and paired t-test were used for statistical analysis. Results: The pre-exercise mean values of LF/HF ratio were significantly higher (p<0.001) in all IBS patients compared to those of control. The post exercise LF/HF ratio were significantly lower (p<0.05) in all IBS patients compared to their pre-exercise values. Conclusion: This study concluded that the sympathovagal balance was towards sympathetic predominance in IBS and regular moderate physical exercise may shift the balance towards parasympathetic predominance in them. Bangladesh Soc Physiol. 2015, June; 10(1): 6-10